2021
DOI: 10.1093/milmed/usab002
|View full text |Cite
|
Sign up to set email alerts
|

US Army Drill Sergeants: Stressors, Behavioral Health, and Mitigating Factors

Abstract: Introduction The role of the drill sergeant is one of the most challenging within the US Army, involving unusually long hours and little time off, for a minimum of 2 years. The current study sought to examine the behavioral health of this population and identify risk factors that might be addressed by policy changes. Materials and Methods In total, 856 drill sergeants across all Army basic training sites completed surveys fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Prolonged exposure to work-related demands without sufficient resources to cope with these demands may lead to chronic exhaustion and cynicism ( Bakker et al, 2014 ). Research has shown that this process may also take place in a military context (e.g., Chappelle et al, 2019 ; Elliman et al, 2021 ; Gottschall and Guérin, 2021 ). Service members in deployment situations, who are exposed to danger and trauma in war, run the risk of developing burnout symptoms when insufficient coping takes place ( Vinokur et al, 2011 ; Delahaij et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged exposure to work-related demands without sufficient resources to cope with these demands may lead to chronic exhaustion and cynicism ( Bakker et al, 2014 ). Research has shown that this process may also take place in a military context (e.g., Chappelle et al, 2019 ; Elliman et al, 2021 ; Gottschall and Guérin, 2021 ). Service members in deployment situations, who are exposed to danger and trauma in war, run the risk of developing burnout symptoms when insufficient coping takes place ( Vinokur et al, 2011 ; Delahaij et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%